Improving Adolescent Knowledge on the Dangers of Smoking and Drug Abuse Through Community-Based Health Education in Kuala Lempuing Village, Bengkulu City - Hermansyah Hermansyah; Mercy Nafratilova; Zadam Marita; Meidyah Pitaloka (Asosiasi Profesi Multimedia Indonesia, 2026)
Background: Cigarette smoking and the abuse of Narcotics, Psychotropics, and Other Addictive Substances (NAPZA) remain major public health issues that negatively impact physical, mental, and social health. Adolescents are particularly vulnerable due to peer influence, environmental exposure, and limited knowledge about the long-term risks of smoking and NAPZA. In RT 11 and RT 12 RW 03, Kelurahan Kuala Lempuing, household smoking and low awareness about NAPZA dangers remain prevalent.Aims: This community service activity aims to increase adolescents’ knowledge and awareness of the dangers of cigarette smoking and NAPZA abuse, as well as prevention strategies.Methods: The intervention was conducted through health education using lectures, discussions, question-and-answer sessions, and informational leaflets. A pre-test and post-test design was applied to 26 participants from RT 11 and RT 12, RW 03, Kelurahan Kuala Lempuing, on December 18, 2025. Data were analyzed descriptively to compare pre-test and post-test scores.Results: Participants’ knowledge improved after the intervention. Before education, smoking knowledge was fair among 53.8% and poor among 46.2% of participants, while NAPZA knowledge was fair among 61.5% and poor among 23.1%. After education, 92.3% of participants achieved good knowledge for both smoking and NAPZA, while 7.7% remained in the fair category.Conclusion: Health education improved community knowledge and awareness regarding smoking and NAPZA and supports ongoing educational programs to reduce smoking and NAPZA use in the target area.